2013
DOI: 10.3136/fstr.19.1029
|View full text |Cite
|
Sign up to set email alerts
|

Purification and Identification of Novel Antioxidant Peptides from Enzymatic Hydrolysate of Ginkgo biloba Seed Proteins

Abstract: Ginkgo biloba seed proteins were hydrolyzed using alkali protease and pepsin to obtain antioxidant peptides. Ginkgo biloba antioxidant peptides (GKAPs) were separated by Sephadex G-25 and Sephadex G-10 gel filtration chromatography. The GKAP B3 exhibited highest antioxidant activity. B3 peptide was separated by reversed-phase high-performance liquid chromatography (RP-HPLC), and 2 peptides with good antioxidant activity, i.e., GKAPs C8 and C9, were obtained. The molecular weight and amino acid sequences of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(7 citation statements)
references
References 24 publications
1
6
0
Order By: Relevance
“…Otherwise, by the DPPH assay, an IC 50 value of both metallic complexes was not achieved at the tested concentrations. Similar activity behaviour was exhibited by GSH in both assays, with IC 50 values consistent to those reported by other authors [18,19]. Ascorbic acid and CAPE were both capable of deactivating ABTS and DPPH radicals in a similar manner, however CAPE showed the highest antioxidant activity with an IC 50 value under 12.5 µM in both assays, with the results in agreement with previous reports [20,21].…”
Section: Chemical Antioxidant Assayssupporting
confidence: 82%
“…Otherwise, by the DPPH assay, an IC 50 value of both metallic complexes was not achieved at the tested concentrations. Similar activity behaviour was exhibited by GSH in both assays, with IC 50 values consistent to those reported by other authors [18,19]. Ascorbic acid and CAPE were both capable of deactivating ABTS and DPPH radicals in a similar manner, however CAPE showed the highest antioxidant activity with an IC 50 value under 12.5 µM in both assays, with the results in agreement with previous reports [20,21].…”
Section: Chemical Antioxidant Assayssupporting
confidence: 82%
“…Only few studies reported the antioxidant, anti-fatigue, and bacteriostatic effects of G. biloba seeds protein isolate (Lena and Philip, 2002; Huang et al, 2010). Wu et al (2013) hydrolyzed Ginkgo peptide with alcalase and pepsin to obtain two antioxidant peptides with an ability to scavenge free radicals and inhibit the lipid peroxidation. However, Ginkgo hypotensive peptides need to be explored further to unravel their underlying mechanisms for higher action.…”
Section: Introductionmentioning
confidence: 99%
“…Their antioxidant potential, expressed as half maximal inhibitory concentrations (IC 50 ), differed depending on the assay applied to measure the activity. Hence, the IC 50 values were at 0.47, 0.51, and 0.53 mg·cm −3 for the YVGD peptide and at 0.46, 0.51, and 0.66 mg·cm −3 for the LGNTDYAVH peptide when measured with DPPH, hydroxyl (·OH), and ·O 2 free radical scavenging activity assays, respectively (Wu and others ).…”
Section: Antioxidant Peptidesmentioning
confidence: 97%
“…Wu and others () hydrolyzed Ginkgo biloba seed proteins using alkaline protease 2709 (Beijing Donghua Qiangsheng Biotechnology Co., Ltd, China) and pepsin (Shanghai Yuanju Biological Technology Co., Ltd., China) to produce the following peptides: YVGD and LGNTDYAVH. Their antioxidant potential, expressed as half maximal inhibitory concentrations (IC 50 ), differed depending on the assay applied to measure the activity.…”
Section: Antioxidant Peptidesmentioning
confidence: 99%